A journey through trans history: from the biomedical field to the activist-social movement - Amigo-Ventureira, Ana María (2019)
The term transsexualism was definited in 1948 by Harry Benjamin, but disruptive behavior in relation to the gender has been documented from ancient times like classical Greece. In this work, a time line it was created. This time line reflects the evolution and the great milestones achieved by the trans collective over time, from an activist-social as well as a psychiatric-medical perspective, analyzing the most relevant events from the 20s to the present.